About the management system of youth business activity in Russia and abroad - R. Ustaev; O. Boris (Вестник Северо-Кавказского федерального университета, 2022)
The purpose of the study is a comparative analysis of existing models of youth entrepreneurship development in Russia and abroad, reflecting their main advantages and disadvantages.   Methods of comparative and historical analysis of information on the state of development and business activity of youth entrepreneurship in Russia and a number of foreign countries are used. Methods of documentation analysis and visual analysis are used. Тhe necessity of transformation of youth entrepreneurship models based on the results of the analysis of youth business activity in entrepreneurship in Russia and abroad has been identified. The system of further development of youth entrepreneurship in Russia may contain a mechanism for the creation of specialized centers in a number of leading subjects of the country. This will increase the degree of entrepreneurial activity among young people, since it implies a certain support for youth entrepreneurship. As a result, it will be possible to talk about the involvement of young people in entrepreneurial activity, an increase in the number of youth projects, and the popularization of entrepreneurship.